Aspects of the biology of the intertidal barnacle Tetraclita serrata Darwin in southern Africa - Delafontaine, M T (Department of Environmental and Geographical Science, 2026)
An important area of research in biology deals with the integration of an organism with its environment. For a long time, interest was focused on the reactions of organisms to their physical milieu (Thiery, 1982). Subsequently, attention shifted to biological interactions such as competition and predation. More recently, biologists have come full circle in that physical aspects are, once again, being more fully investigated (e.g. Kazmierczak et al., 1985; Underwood, 1985). Shorelines provide an environment perhaps most ideally suited to such investigations. The transition zone between sea and land represents a unique mosaic of physical conditions whose diversity has yet to be fully explored by biologists. This is exemplified by classical models of species distributions involving 'wave action' (see Newell, 1979), a factor which is rarely precisely quantified in biological practice although its individual, hydrodynamic components have long been known to physical oceanographers. The present study of the biology of a rocky intertidal organism, th~ barnacl~ Tetraclita serrata Darwin, was carried out in southern Africa'between 1976 and 1984 with the specific aim of revealing the most important relationships between this organism and its physical milieu. The region is ideally suited for this purpose because a number of distinctly different climatic regimes occur along the South African coast. Thus, the cold-temperate western region is influenced predominantly by the cold Benguela Current (Fig. 1 ), whereas the warm Agulhas Current co.ntributes to the warmtemperate conditions on the south coast, merging into the subtropical environment of the east coast. In addition, an often rugged shoreline provides a multitude of microhabitats in which local physical conditions vary dramatically over very small distances.